Impact Of Gold Price On Stock Market Return on NSE: An Empirical Analysis - Jacob, Tom; Paul, Thomas; Kattookaran, (Gyan Management Journal, 2019)
The financial system of a country is an important tool for economic development of the country as it helps in the creation of wealth by linking savings with investments. It facilitates the flow of funds from the households (savers) to business firms (investors) to aid in wealth creation and development of both the parties. In our stock broking industry there are many investors who are investing money in various investment options, but large amount of investment is done in equity market and gold market. This study analyse the impact of gold price variation affect the stock market returns in India. Unit root test indicates that the time series data are not stationary at levels and stationary at 1st difference. Johansen's Co-integration maximum likelihood method is employed to test the long run relationship between gold price and stock market return in India. Vector Error Correction Model (VECM) was employed to describe the dynamic interrelationship among the variables of the model. On the basis of the empirical result gold price is negatively statistically significant for influencing the domestic stock market return.
Keywords: ANR; Gold Price; VECM; ADF; AIC